Price, performance and expectations as determinants of customer satisfaction in a low price-high quality hotel - Ahmad, Sabri (1999)
In this study, the model describes the impact of price, performance and expectations on satisfaction, is tested. The results suggest that pre-price and pre-performance expectations do not play important roles in determining customer satisfaction in a low price/high quality hotel industries. Post-price and post-performance perceptions simultaneously play leading roles in determining satisfaction. These findings offer new insights pertaining to marketing for using price-based strategies to enhance customer satisfaction. Future research directions and managerial implications of the findings are outlined.